Profiling of total fatty acid content during jatropha seed development - Nur Azlan, Bin Yusuf (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Jatropha curcas is a potential source of vegetable oil in production of biodiesel. Enzyme such as stearoyl-acyl carrier protein desaturase (ACP) plays major role in catalyzing production of monounsaturated fatty acid that important for a good biodiesel characteristics. This experiment is conducted to investigate which period is the most valuable for the seed of J. curcas actively synthesizing fatty acids. This involves oil extraction of seeds from different intervals of seed development after anthesis and analysis with Proton Nuclear Magnetic Resonance (H-NMR) and Fourier Transform Infrared Spectrometry (FT-IR). Seed of yellow fruit has the highest oil content and most stages of fruit possessed unsaturated fatty acids. The highest concentration of unsaturated fatty acid is at stage IV (ripe yellow fruit). The presence of Fatty Acid Methyl Ester (FAME) can be detected at 3.81 ppm signal under H-NMR verification after transesterification with potassium hydroxide (KOH)-catalyzed methanolysis without reflux method with little modifications on original protocol. This is important for further analysis through Gas Chromatography (GC) to determine the percentage composition of fatty acid.